Bracing configuration and seismic performance of reinforced concrete frame with brace. (26th April 2017) - Qiao, Shengfang; Han, Xiaolei; Zhou, Kemin
Summary: Brace has been used to improve structural seismic performance in reinforced concrete (hereafter called RC) frame extensively. However, the reasonable bracing configurations were not highlighted. And the brace buckling was not considered. Bracing configurations and seismic performance of RC frame with brace are studied in this paper. First, optimized bracing configurations of entire structures and 1‐story 1‐span structures are derived by topology optimization using truss‐like material model. Next, the structure models are simulated in OpenSees. Moreover, different bracing configurations are employed. Last, seismic performance and seismic response of RC frame structures with brace are discussed using static nonlinear analysis and dynamic time–history analysis, and brace buckling is considered. The numerical results indicate that more details for manufacturing or constructing can be presented by bracing configuration using truss‐like model. Further, the increase of structural strength and stiffness is more advisable in bracing configuration using topology optimization (hereafter called TPB), which corresponds to optimized result using entire structure than other configurations. The optimized bracing configuration based on 1‐story 1‐span structure is also beneficial within the prescribed conditions. Moreover, the brace buckling can decrease both strength and stiffness, and the buckling can also aggravate the damage extent than the brace without buckling.